Tuning the microstructure, martensitic transformation and superelastic properties of EBF3-fabricated NiTi shape memory alloy using interlayer remelting. (August 2022) - Li, Binqiang; Wang, Liang; Wang, Binbin; Li, Donghai; Oliveira, J.P.; Cui, Ran; Yu, Jianxin; Luo, Liangshun; Chen, Ruirun; Su, Yanqing; Guo, Jingjie; Fu, Hengzhi
Graphical abstract: Highlights: Interlayer remelting strategies can regulate the microstructure evolution, martensitic transformation, and superelasticity of EBF 3 -fabricated NiTi SMAs. A one-step reversible transformation (B2 ↔ B19′) occurred upon heating/cooling. The critical stress (σ Ms ) has a strong dependence on the martensitic transformation behavior. The broadening and stabilization of martensite is the key factor for the deterioration of the superelastic response. Abstract: In this work, different interlayer remelting strategies are applied to regulate the microstructure evolution, martensitic transformation, and superelastic features of NiTi shape memory alloys prepared using the EBF 3 additive manufacturing technique. The NiTi deposits prepared under different remelting beam currents are all composed of the B2 austenite, residual B19′ martensite, and submicron-scale Ti4 Ni2 O x precipitates, and exhibit a one-step phase transformation (B2 ↔ B19′). Meanwhile, the crystallographic orientation, grain boundaries, and residual strain of these alloys present a distinct variation with the application of different remelting beam currents. During mechanical testing, the critical stress (σ Ms ) of the EBF 3 -fabricated NiTi alloys was seen to possess a significant dependence on the martensitic transformation behavior, namely with the amount of B19′ martensite and the corresponding Ms . However, the broadening and stabilization of lamellar martensite created by dislocation pile-ups and plastic deformation in the cyclic loading–unloading procedure is the key reason for the deterioration of the superelastic response of the NiTi deposits. This work confirms that the mechanical and functional performances of NiTi alloys produced via EBF 3 -technique can be modified upon the application of proper interlayer remelting strategies, which can be extrapolated to the directed energy deposition of shape memory alloys or other metal components.